Flexible Borders. Gender, Journalism and Political Sociability in Pergamino (Buenos Aires, Argentina, 1946-1953) - de Arce, Alejandra; Salomón, Alejandra (Universidad Pedagógica y Tecnológica de Colombia, 2017)
After the first Peronist government (1946-1952), the Feminine Suffrage Law of 1947 and the leadership of Eva Perón accentuated the political movilization of women and their institutionalization in the party. In 1949, the creation of the Peronist Feminine Party as an autonomous force was followed by the founding of independent basic feminine units, formally separated from masculine units by specific regulations. Nevertheless, in rural localities, there is evidence of relations between masculine and feminine public spaces, established through informal rules based on personal neighboring and family connections marked by trust and reciprocity. The existance of very diffuse borders between public and private spaces in rural sociability contributed to this phenomenon. This integration of genders in spaces for social and political action deserves a specific analysis. The present study reflects on the relations that existed between the different branches of the Peronist movement, by means of a micro-historical approach based on the analysis of life stories, photographs, personal archives, press and party documents.